2009
DOI: 10.1063/1.3077170
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and chemical properties of molybdenum oxide doped hole injection layers in organic light emitting diodes

Abstract: The origins of barrier lowering leading to high efficient organic light emitting devices with incorporation of molybdenum oxide (MoOx) in anode structures are investigated. Ultraviolet and x-ray photoemission spectra reveal that p-type doping effects in the organic films and carrier concentration increase at the anode interfaces cause the hole injection barrier lowering. The gap states, which help carrier injection from the anodes, resulted from the oxygen deficiency in MoOx due to the interaction of organic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 21 publications
3
29
1
Order By: Relevance
“…The hole injection barrier decreases from 2.78 to 0.53 eV owing to the presence of the defect state (gap state) in MoO 3Àx . This result is consistent with the previous report on the MoO 3Àx /ITO interfaces [21,22], and provides useful guidance in fabricating organic electronic devices using graphene as anode and MoO 3Àx as HIL. Charge density q (a. u) Thickness of MoO 3-x films (nm) …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The hole injection barrier decreases from 2.78 to 0.53 eV owing to the presence of the defect state (gap state) in MoO 3Àx . This result is consistent with the previous report on the MoO 3Àx /ITO interfaces [21,22], and provides useful guidance in fabricating organic electronic devices using graphene as anode and MoO 3Àx as HIL. Charge density q (a. u) Thickness of MoO 3-x films (nm) …”
Section: Discussionsupporting
confidence: 92%
“…Among the oxides, MoO 3 is the most studied because of its easy processing and relatively high refractive index [18,19]. Several reports showed that the performance of organic electronic devices increased with the introduction of MoO 3 HIL [20,21]. The HIL is essential for better band alignment between the anode and organic hole transport layer in OLED or OPV devices.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the organic-inorganic heterojunction can improve the physical contact between the metal electrode and organic film, which was widely applied in OFET and organic diodes. [20][21][22][23][24][25][26] …”
Section: Effect Of Organic-inorganic Heterojunctionsmentioning
confidence: 99%
“…16,17 Inorganic materials have also been introduced into various organic electronic devices. [18][19][20][21][22][23][24][25] For example, pentacene/ zinc oxide ͑ZnO͒ bilayer transistors with different operation modes have been obtained by varying the thickness of ZnO layer. 19 Transition metal oxides are often used as a buffer layer between organic semiconductor and metal for performance enhancement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation